ANALYSIS OF THE INFLUENCE OF HOSPITAL MANAGEMENT INFORMATION SYSTEM WITH STRUCTURAL EQUATION MODELING APPROACH (Case Study of Regional Hospital RAA Soewondo Pati) - Murti Wisnu Ragil Sastyawan; Loekas Soesanto; Bambang Purwanggono; Arfan Bakhtiar (Proceeding of The International Conference on Business and Economics, 2023)
The information system is one of the strategic means in patient care-oriented management. So far, Regional Hospital RAA Soewondo Pati has never conducted an evaluation related to the management information system (HMIS), so it is not known that the existing system is effective and efficient to answer patient needs. The purpose of this study was to determine the effect of the hospital management information system with the structural equation modeling method approach. This research is a case study research with data collection method using a questionnaire. The data that has been collected is then analyzed using SEM analysis. The results of his research stated that the quality of the system had a significant positive effect on the use of information systems. There is a significant effect of system quality on user satisfaction. There is a significant positive effect between the quality of information on the intensity of the use of information. In this study, the intensity of the use of information systems does not play a role in increasing user satisfaction in using information systems. User satisfaction has a significant positive effect on net benefits.